Prevalence and risk factors for lameness in insulated free stall barns in Finland - Sarjokari, Kristiina; Kaustell, Kim O.; Hurme, Timo; Kivinen, Tapani; Peltoniemi, Olli A. T.; Saloniemi, Hannu; Rajala-Schultz, Päivi J. (Elsevier, 2013)
Lameness is a painful condition that alters physiology and behavior of dairy cattle. The main objective of this study was to explore the prevalence of lameness in dairy cows, and its association with housing and herd management. Another aim was to identify poorly functioning structures and equipment that may contribute to increased lameness. Data on herd management, and barn design and functionality were collected in 87 herds, and the gait of 3459 cows was scored. Of the cows scored, 23% were lame (lameness scores 3–5; from slightly abnormal gait to severe lameness). The median within-herd lameness prevalence was 21%, ranging from 2 to 62%. The association between cow level lameness risk and cow specific risk factors was modeled with a logistic regression analysis. The odds ratio (OR) for lameness was for Holstein cows 1.6 (CI 1.3–1.9) times higher than for Ayrshire cows. Second and 3+parity cows were more likely to be lame than first lactation cows; OR 2.1 (CI 1.7–2.8) and 6.0 (CI 4.8–7.7), respectively. A herd level lameness prevalence estimate, accounting for the effects of cow’s breed and parity, was used as an outcome in modeling housing and management related risk factors. Lameness prevalence was lower in herds with a feed barrier divided to separate feeding places (0.17), compared to the ones with a post-and-rail (0.24). The lameness estimate was higher in herds with very slippery floors (0.31) than in herds with slightly slippery (0.16) or firm floors (0.16). The prevalence of lameness was associated with the width of a walking alley next to the feeding table, being 0.17 for herds that had alleys wider than 340 cm, and 0.23 for herds with an alley narrower than 320 cm. Lameness estimate (0.18) was lower if water was supplied from water cups only compared to water being supplied water from both cups and troughs (0.23). Most farmers had not adjusted neck and front rails properly in stalls, and had hard stall surfaces, compromising cow comfort. More than a half of the studied herds had problems with manure removal and urine drainage. Those findings suggest that there is a great need to educate dairy farmers and construction planners of the benefits and factors contributing to claw and leg health. Also, more emphasis should be placed to proper manure removal and urine drainage.
Keywords: Kotieläintuotanto, mehiläistalous, riistanhoito, kalatalous; free stalls; liikuntaelinten taudit; navetat; lehmät; housing; dairy cow; lameness